2022
DOI: 10.1002/capr.12542
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of psychologists' experiences of teletherapy within the Irish Public Mental Health System

Abstract: Objective The current qualitative study aimed to investigate psychologists' experiences of teletherapy throughout the COVID‐19 pandemic, with a particular focus on teletherapy's impact on therapeutic relationships. Method Fifteen participants, consisting of clinical and counselling psychologists employed by the Health Service Executive (HSE) in Ireland, participated in semi‐structured interviews conducted via telephone. Results Constructionist thematic analysis yielded three prominent themes: (i) psychologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
(56 reference statements)
2
8
0
Order By: Relevance
“…High satisfaction rates may also be explained by the growing familiarity and level of comfort with video communication technologies in the general population, which increased due to COVID-19 social movement restrictions. As previous studies (Aafjies-van Doorn et al, 2021;Reilly et al, 2022) have identified perceptions held toward video chat as a lesser quality service than in person, further research could also investigate the factors contributing to participant and therapist views that infer video chat to be an acceptable substitute rather than equal modality to in-person service.…”
Section: Discussionmentioning
confidence: 97%
“…High satisfaction rates may also be explained by the growing familiarity and level of comfort with video communication technologies in the general population, which increased due to COVID-19 social movement restrictions. As previous studies (Aafjies-van Doorn et al, 2021;Reilly et al, 2022) have identified perceptions held toward video chat as a lesser quality service than in person, further research could also investigate the factors contributing to participant and therapist views that infer video chat to be an acceptable substitute rather than equal modality to in-person service.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, the beliefs were that: Internet-based therapies do not have a strong evidence base; they are less effective than in-person therapy; there is a decreased ability to develop a strong therapeutic alliance digitally; dMH interventions are not suitable for severe mental health problems; and Internet-based therapies will fail to meet clients' expectations of therapy. Thew (2020) Gerton et al, 2022;Poletti et al, 2021;Reilly et al, 2022). With experience, therapists come to view video chat telehealth as effective and comparable to face-to-face services.…”
Section: Therapist Assistance Within Dmh Interventions Has Been Deliv...mentioning
confidence: 99%
“…The research conducted to date suggests that therapist perceptions of video chat use within dMH interventions tend to become more positive with experience and are predictive of future adoption into practice (Aafjies‐van Doorn et al, 2021; Connolly et al, 2019; Gerton et al, 2022; Poletti et al, 2021; Reilly et al, 2022). With experience, therapists come to view video chat telehealth as effective and comparable to face‐to‐face services.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was a qualitative exploration of service users' experiences of teletherapy in a public setting during the COVID‐19 pandemic in Ireland, providing a rich insight into these experiences to inform its future applications. It is one part of a larger study exploring experiences of teletherapy, with Reilly et al (2022) exploring therapists' experiences. Note that the terms “service user” and “client,” and “psychologist” and “therapist,” will be used interchangeably throughout this report, to reflect the terminology used by participants and authors of referenced works.…”
Section: Introductionmentioning
confidence: 99%